Comparison of various rehabilitation methods applied in patients with chronic obstructive pulmonary disease - Szeliga, Ewa; Bal-Bocheńska, Monika; Czenczek, Ewelina (European Journal of Clinical and Experimental Medicine, 2011)
<section id="block-views-streszczenie-block" class="block block-views clearfix" style="box-sizing: border-box; display: block; color: #666666; font-family: Lato, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Introduction: Chronic obstructive lung disease is one of the most frequent respiratory system diseases. It includes chronic bronchitis and pulmonary emphysema. The symptoms of this disease may be the following: a cough with a lot of mucus, excessive mucus expectoration, dyspnea, limited air flow in respiratory tracts and gas exchange impairment. Physiotherapy plays an important part in treating COPD. The role of physiotherapy is complex and includes prevention, education of patients, evaluation of function, psychosocial influence and various trainings improving lung ventilation, simultaneously, improving the quality of the patients’ life. Aim of the research: The aim of the research was the evaluation of the influence of applied physiotherapeutic methods on the health of patients diagnosed with chronic obstructive pulmonary disease. Material and method: The examined group included the patients with COPD, hospitalized in the Specialist Hospital of Tuberculosis and Lung Diseases in Rzeszów. The patients were treated in the following hospital units: Pulmonology and Chemotherapy Ward, Pulmonology and Allergology Ward and Tuberculosis Ward. Two groups of patients were compared. Each of the group consisted of 35 people, in the first group Respiflo Fs device was used, while in the second group a bottle filled with water was used to create positive pressure in respiratory tracts. Results: On the basis of the conducted research it was proved that in the first and in the second group of patients, the function of lungs improved significantly. Only in few cases the improvement was not observed. However, there was no case of function deterioration. Conclusions: 1. In the examined group, it was shown that the rehabilitation process had significant, positive influence on the health of people with chronic obstructive pulmonary disease. 2. Positive influence of rehabilitation on the quality of life of the examined people was also demonstrated.